Ion potential in non‐ideal dense quantum plasmas. Issue 10 (27th December 2017) - Moldabekov, Zh.A.; Groth, S.; Dornheim, T.; Bonitz, M.; Ramazanov, T.S.
Abstract : The screened ion potential in non‐ideal dense quantum plasmas is investigated by invoking the Singwi–Tosi–Land–Sjölander approximation for the electronic local field correction at densities r s ≲ 2 and degeneracy parameters θ ≲ 1, where rs is the ratio of the mean inter‐particle distance to the first Bohr radius, and θ is the ratio of the thermal energy to the Fermi energy of the electrons. Various cross‐checks with ion potentials obtained from ground‐state quantum Monte Carlo data, the random phase approximation, and with existing analytical models are presented. Furthermore, the importance of the electronic correlation effects for the dynamics in strongly coupled ionic subsystems for 0.1 ≤ rs ≤ 2 is discussed.